Verhuellia is a segregate lineage in Piperaceae: more evidence from flower, fruit and pollen morphology, anatomy and development - Samain, Marie-Stéphanie (Oxford University Press, 2010)
BACKGROUND AND AIMS: The perianthless Piperales, i.e. Saururaceae and Piperaceae, have simple reduced flowers strikingly different from the other families of the order (e.g. Aristolochiaceae). Recent molecular phylogenies proved Verhuellia to be the first branch in Piperaceae, making it a promising subject to study the detailed structure and development of the flowers. Based on recently collected material, the first detailed study since 1872 was conducted with respect to morphology, anatomy and development of the inflorescence, pollen ultrastructure and fruit anatomy. METHODS: Original scanning electron microscopy (SEM), transmission electron microscopy (TEM) and light microscopy (LM) observations on Verhuellia lunaria were compared with those of Piperaceae, Saururaceae and fossils. KEY RESULTS: The inflorescence is an indeterminate spike with sessile flowers, each in the axil of a bract, developing in acropetal, helical succession. Flowers consist of two (occasionally three) stamens with basifixed tetrasporangiate anthers and latrorse dehiscence by a longitudinal slit. The gynoecium lacks a style but has 3–4 stigma branches and a single, basal orthotropous and unitegmic ovule. The fruit is a drupe with large multicellular epidermal protuberances. The pollen is very small, inaperturate and areolate, with hemispherical microechinate exine elements. CONCLUSIONS: Despite the superficial similarities with different genera of Piperaceae and Saururaceae, the segregate position of Verhuellia revealed by molecular phylogenetics is supported by morphological, developmental and anatomical data presented here. Unitegmic ovules and inaperturate pollen, which are synapomorphies for the genus Peperomia, are also present in Verhuellia.